Assessing Direct Marketing and Personal Selling Tools Used by Medical Representatives - Kyguolienė Asta; Juknė Gabrielė (Organizacijų Vadyba: Sisteminiai Tyrimai)
Direct marketing and personal selling tools are the tools most used by medical representatives in their daily work. The aim of the study is therefore to assess the direct marketing and personal selling tools used by medical representatives and to provide recommendations for their effective use. The research includes results from a questionnaire survey of healthcare professionals and semi-structured interviews with medical representatives. Based on the findings, the article provides insights into what changes might be useful in the use of direct marketing and personal selling tools.